GEOMETRIC PLANNING AND THICK PAVEMENT ON ALTERNATIVE ROAD KM 171 TANAH BUMBU REGENCY - Karimah, Mariatul; Prakoso, Puguh Budi (CERUCUK, 2026)
Road Geometric Planning is planning the overall road trase along with its alignment. AASHTO and Highways are the two geometric road planning standards to be used. Satui STA Ring Road 0+000-2+245 was chosen in this planning because it is a new alternative road from KM 171 Road which has been damaged due to mining activities. The speed of the road plan is 60 km / h with flat road terrain conditions. The purpose of this study is to assess whether the existing horizontal infrastructure plan meets the standards of Highways. This research will also provide alternative designs of horizontal and vertical alignments with the help of Autocad Civil 3D 2022 software and plan the design of thick pavements.For geometric planning the road uses AASHTO 2011 standards, but for the study criteria used is Highways 2021. Meanwhile, for thick pavement planning using MDP 2017 regulations. In this study, data collection was carried out in the form of Literature Studies, Primary Data and Secondary Data.Based on the results of the analysis, there were 12 bends in the horizontal alignment reviewed and 9 bends that did not meet the requirements for horizontal alignment planning. The alternative design provided produces a trase of 2+253 km with a horizontal alignment of 10 bends with Full Circle (FC) and Spiral-Circle-Spiral (S-C-S) bend types, as well as 44 vertical alignments consisting of 26 concave and 18 convex arches. Analysis of the results of the calculation of road pavement thickness with MDP 2017 guidelines, namely AC-WC = 40 mm, AC-BC = 60 mm, AC-Base = 160 mm, and LPA = 300 mm. Keywords: Road Geometrics, AutoCAD Civil 3D 2022, Build Marga, Road Violence